Osteoid Osteoma of the Distal Humerus Mimicking Sequela of Pediatric Supracondylar Fracture: Arthroscopic Resection—Case Report and A Literature Review - Jordi Font Segura; Sergi Barrera-Ochoa; Albert Gargallo-Margarit; Eva Correa-Vázquez; Anna Isart-Torruella; Xavier Mir Bullo (Case Reports in Medicine)
Osteoid osteoma (OO) is a small and painful benign osteoblastic tumour located preferentially in the shaft of long bones near the metaphyseal junctions, with a predilection for the lower limbs. Juxta- and intra-articular OOs are rare and even though hip, elbow, and talus are the most commonly reported locations, they may be found in any joint accounting for approximately 13% of all osteoid osteomas. There is usually a significant time delay between symptom initiation and diagnosis when the lesion is present in an uncommon location due to the diagnostic challenge it presents due to the lack of classical clinical signs and/or radiographic features found in the extra-articular lesions. A case of a distal humerus OO of a 15-year-old girl is presented to point out that a confounding factor, such as a previous paediatric supracondylar fracture, may further delay the already difficult diagnosis of a juxta- or intra-articular osteoid osteoma and also to emphasize the possibility of arthroscopic treatment of such lesions.